SYNTHESIS OF NEW BENZOTHIAZOLYL-PHENOTHIAZINE DERIVATIVES - BRÉM, Balasz; GÁL, Emese; CRISTEA, Castelia; GĂINĂ, Luiza; GROZAV, Adriana; ZAHARIA, Valentin; SILAGHI-DUMITRESCU, Luminiţa (Studia Universitatis Babeș-Bolyai Chemia, 2015)
A series containing 1-, 2-, 3- and 4-(benzothiazol-2yl)-10Hphenothiazine derivatives was advantageously prepared by the condensation of each corresponding phenothiazine-carbaldehyde regioisomer with 2-amino-benzenethiol. The reaction conditions were optimized and the structures of the new compounds were unambiguously assigned based on high resolution nuclear magnetic resonance spectroscopy and mass spectrometry.